Optimization of Thermophysical and Rheological Properties of Mxene Ionanofluids for Hybrid Solar Photovoltaic/Thermal Systems - Balaji Bakthavatchalam; Khairul Habib; R. Saidur; Navid Aslfattahi; Syed Mohd Yahya; A. Rashedi; Taslima Khanam (Nanomaterials, 2021)
Since technology progresses, the need to optimize the thermal system’s heat transfer efficiency is continuously confronted by researchers. A primary constraint in the production of heat transfer fluids needed for ultra-high performance was its intrinsic poor heat transfer properties. MXene, a novel 2D nanoparticle possessing fascinating properties has emerged recently as a potential heat dissipative solute in nanofluids. In this research, 2D MXenes (Ti3C2) are synthesized via chemical etching and blended with a binary solution containing Diethylene Glycol (DEG) and ionic liquid (IL) to formulate stable nanofluids at concentrations of 0.1, 0.2, 0.3 and 0.4 wt%. Furthermore, the effect of different temperatures on the studied liquid’s thermophysical characteristics such as thermal conductivity, density, viscosity, specific heat capacity, thermal stability and the rheological property was experimentally conducted. A computational analysis was performed to evaluate the impact of ionic liquid-based 2D MXene nanofluid (Ti3C2/DEG+IL) in hybrid photovoltaic/thermal (PV/T) systems. A 3D numerical model is developed to evaluate the thermal efficiency, electrical efficiency, heat transfer coefficient, pumping power and temperature distribution. The simulations proved that the studied working fluid in the PV/T system results in an enhancement of thermal efficiency, electrical efficiency and heat transfer coefficient by 78.5%, 18.7% and 6%, respectively.